The Role of Electronic Word of Mouth in Mediating the Influence of Social Media on Brand Image and Brand Trust - Evelyn, Patriciaa; Arief, Muhammad; Baskara, Ika (PT Inovasi Pratama Internasional, 2025)
The rapid development of technology and information currently encourages coffee shop entrepreneurs to utilize social media as a marketing platform, especially through electronic word of mouth (E-WOM), in conveying information about their products and business premises. An effective viral marketing strategy through social media plays an important role in building a brand image that can influence brand trust. This study aims to analyze the influence of social media, E-WOM, and brand image on increasing brand trust. This study was conducted in Bekasi with a descriptive causality research design, using a quantitative approach and purposive sampling technique. The research data were collected from 175 respondents targeting active Instagram users as the general population and Kopi Tuku lovers in Bekasi as the specific population. The conceptual model analysis was conducted using Path Analysis using the Statistical Package for the Social Sciences (SPSS). The results showed that social media significantly increased E-WOM and brand image. E-WOM was proven to increase brand image and brand trust, while brand image also directly increased brand trust. In addition, social media has a positive influence on brand image and brand trust through E-WOM mediation. This study provides an important contribution for coffee shop entrepreneurs in developing social media-based marketing strategies. By utilizing E-WOM and building a strong brand image, business actors can increase brand trust, which ultimately encourages interest in purchasing products and visits to business premises.